2018
DOI: 10.5530/pj.2018.4.113
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antidiabetic Potential of Galing Stem Extract (Cayratia trifolia Domin)

Abstract: Galing (Cayratia trifolia Domin.) have been used empirically to treat various diseases, one of them is antidiabetic. Objective: To determine the phytochemical content and the activity of the ethanol extract of the galing stem as antioxidant and antidiabetic. Method: The galing stem extract was investigated for phytochemical by Thin Layer Chromatography (TLC) and its antioxidant activity using DPPH scavenging activity assay. In vivo, antidiabetic test was conducted by animal diabetes modeling that has given str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The works of Shikha [54] showed that in diabetic rats, both the doses (200 mg/kg and 400 mg/kg) of ethyl acetate extract were found to be significant (P <0.05) when compared with control and favourable changes in biochemical parameters were also observed [54]. In contrast the in vivo, antidiabetic test conducted by animal diabetes modeling that has given streptozotocin 150 g/kg BW and 10% of sucrose solution intraperitoneally showed that the effect of extract 400 and 500 mg/kg BW are not different significantly with glibenclamide in reducing blood glucose levels subset of the statistics ANOVA (p> 0.05) [55].…”
Section: Cayratia Trifoliamentioning
confidence: 87%
“…The works of Shikha [54] showed that in diabetic rats, both the doses (200 mg/kg and 400 mg/kg) of ethyl acetate extract were found to be significant (P <0.05) when compared with control and favourable changes in biochemical parameters were also observed [54]. In contrast the in vivo, antidiabetic test conducted by animal diabetes modeling that has given streptozotocin 150 g/kg BW and 10% of sucrose solution intraperitoneally showed that the effect of extract 400 and 500 mg/kg BW are not different significantly with glibenclamide in reducing blood glucose levels subset of the statistics ANOVA (p> 0.05) [55].…”
Section: Cayratia Trifoliamentioning
confidence: 87%
“…Sistem imun spesifik diperankan oleh limfosit B dan limfosit T dengan perbandingan 1:5. Limfosit B bertanggung jawab terhadap respon imun yang dimediasi antibodi (Yusuf, Susanty, Susanty, & Fawwaz, 2018). Selain memiliki kemampuan mengenali antigen secara spesifik, imfosit B bertanggung jawab membentuk antibodi humoral dalam darah yang juga dikenal sebagai immunoglobulin (M. Y.…”
Section: Hasil Dan Pembahasanunclassified
“…It is potential as an antioxidant with the IC50 61,52 mg/L which indicated that the extract had strong antioxidant. 33…”
Section: Antioxidant Activity: -mentioning
confidence: 99%